Comparison of allogeneic T cell-depleted peripheral blood stem cell and bone marrow transplantation: effect of stem cell source on short- and long-term outcome. - Barge, R; Brouwer, R; Beersma, M; Starrenburg, C; Zwinderman, A; Hale, G; Waldmann, H; den Ottolander, G; Falkenburg, J; Willemze, R; Fibbe, W (2001)
We report the results of a retrospective single-center study comparing engraftment, acute and chronic GVHD, relapse and survival in patients with malignant hematological disorders transplanted with allogeneic peripheral blood stem cells (alloPBSCT, n = 40) or bone marrow cells (alloBMT, n = 42). All transplants were T cell depleted by in vitro incubation with the Campath-1 monoclonal antibody. Primary graft failure occurred in none of the patients receiving an alloPBSCT compared with 3/42 of the recipients of an alloBMT. In addition, two patients in the alloBMT group showed no platelet engraftment. Recipients of PBSC had a more rapid recovery of neutrophils (median 14 days) compared to BM transplant recipients (median 32 days). Platelet recovery was also accelerated in PBSC recipients compared to BM recipients (11 vs 38 days). There was an increase in the incidence of grade II acute GVHD and chronic GVHD in patients after alloPBSCT (18% and 23%, respectively) compared to patients receiving alloBMT (5% and 8%, respectively). The 2-year cumulative incidence of relapse was similar in both groups (47%). At 6 months after transplantation, transplant-related mortality (TRM) was lower in PBSCT recipients than in BMT recipients. However, at a follow-up of 3 years TRM was similar in both groups. The disease-free survival rate at 3 years after transplantation did not differ between the groups (42% for PBSCT and 41% for BMT recipients). Our results indicate that T cell-depleted alloPBSCT compared to alloBMT is associated with a more rapid hematopoietic reconstitution and a decreased TRM at 6 months follow-up after transplantation. However, at a follow-up of 3 years, no sustained survival benefits were observed.